Algebras of unbounded operators over the ring of measurable functions and their derivations and automorphisms - Albeverio, S.; Ayupov, Sh. A.; Zaitov, A. A.; Ruziev, J. E. (Methods of Functional Analysis and Topology, 2009)
In the present paper derivations and *-automorphisms of algebras of unbounded operators over the ring of measurable functions are investigated and it is shown that all L^0-linear derivations and L^0-linear *-automorphisms are inner. Moreover, it is proved that each L^0-linear automorphism of the algebra of all linear operators on a bo-dense submodule of a Kaplansky-Hilbert module over the ring of measurable functions is spatial.